Mixed culture of Pacific white shrimp Litopenaeus vannamei (Boone, 1931) and flathead grey mullet Mugil cephalus (Linnaeus, 1758) in floating cages - Ghosh, Shubhadeep; Ranjan, Ritesh; Megarajan, Sekar; Pattnaik, Phalguni; Dash, Biswajit; Edward, Loveson (Indian Journal of Fisheries, 2016)
The study explored the possibility of integrating the grey mullet Mugil cephalus (Linnaeus, 1758) along with Pacific white shrimp  Litopenaeus vannamei (Boone, 1931) in floating cage culture in Godavary Estuary, India. Post-larvae (PL 12) of L. vannamei (3 lakhs nos.), were acclimatised and nursed in five hapas for 28 days at a density of 3333 nos. m-2, with survival of 60%. L. vannamei juveniles having mean weight of 0.86 g, stocked at a density of 1060 nos. m-2, were cultured along with and without pre-stocked M. cephalus, in three floating cages each. Six thousand fry of M. cephalus (mean length 4.17 cm; mean weight 1.22 g) were stocked in three cages at uniform density of 23.5 nos. m-3, three months prior to stocking of L. vannamei. Shrimps were fed commercial pellets @ 3-8% of body weight, four times daily and harvested after 68 days. Fishes were fed with pelleted feed and after five months attained mean length of 23.7 cm and mean weight of 274.1 g. Survival was 46.4% and the average production obtained was 250.2 kg. At harvest, L. vannamei in monoculture system attained mean weight of 13.3 g and in the mixed culture system, average weight obtained for the shrimps was 13.5 g. Survival, feed conversion ratio (FCR) and production of L. vannamei from monoculture were 64.7%, 2.0 and 258.9 kg and from mixed culture 76.8%, 1.6 and 311.5 kg respectively. Daily weight increment and specific growth rate (SGR) of L. vannamei was 0.18 g and 4.06 for monoculture and 0.19 g and 4.01 for mixed culture, resepectively. Feed conversion, survival and production of L. vannamei were significantly (p